2000
DOI: 10.1097/00004872-200018070-00002
|View full text |Cite
|
Sign up to set email alerts
|

The role of size at birth and postnatal catch-up growth in determining systolic blood pressure

Abstract: Both birth weight and head circumference at birth are inversely related to systolic blood pressure. The relationship is present in adolescence but attenuated compared to both the pre- and post-adolescence periods. Accelerated postnatal growth is also associated with raised blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

62
703
14
15

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 961 publications
(794 citation statements)
references
References 84 publications
62
703
14
15
Order By: Relevance
“…Similarly, elevated blood pressure in youth may be a response to fetal under nutrition, causing long-term changes in arterial structure in the child. 34,35 In our study, we observed a high prevalence of parental smoking. Maternal smoking is a major risk factor for low birth weight; furthermore paternal smoking also carries risk for the fetus.…”
Section: Discussionsupporting
confidence: 49%
“…Similarly, elevated blood pressure in youth may be a response to fetal under nutrition, causing long-term changes in arterial structure in the child. 34,35 In our study, we observed a high prevalence of parental smoking. Maternal smoking is a major risk factor for low birth weight; furthermore paternal smoking also carries risk for the fetus.…”
Section: Discussionsupporting
confidence: 49%
“…[1][2][3] However, the magnitude of these associations is relatively modest -BP increases approximately 2 mm Hg per kg decrease in birth weight, and o1 mm Hg per 1-week decrease in the length of gestation. [2][3][4] This is in marked contrast with much stronger relationships between smaller body size at birth and prevalence of overt hypertension, 5 coronary heart disease [6][7][8] and stroke, 9 and also in contrast with the recently reported associations of shorter length of gestation with stroke 10 and cerebrovascular disease. 11 One possible explanation for this discrepancy is that, rather than the absolute level of BP, it is cardiovascular reactivity that is associated with small size at birth and shorter length of gestation.…”
Section: Introductionmentioning
confidence: 71%
“…K Evidence exists for an inverse relationship between birth weight and blood pressure, both in adults [3][4][5][6] and in children. 8-11 K Less is known regarding the potential link between being born early, independent of birth size, and subsequent blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…2 In particular, a number of epidemiological studies have demonstrated a negative correlation between birth weight and blood pressure in adulthood. [3][4][5][6] It has been estimated that a 1 kg higher birth weight is typically associated with a 2-4 mm Hg lower systolic blood pressure. 7 Evidence also exists for such a relationship in childhood, [8][9][10][11] but it has been suggested to vary with age and gender.…”
Section: Introductionmentioning
confidence: 99%